Effect of Herbal Plant Extracts on the Economic Parameters of Silkworm Bombyx mori L. - Sithi Jameela, Muthu Mohamed; Ponanthi, Karnan; Chitra Devi, Murugesan; Ramesh Kumar, Senthur Pandi (INTI International University, 2023)
Background: In the unorganized sector, the silk industry has grown to become a well-liked cottage business that employs more than 10 million rural residents. The development of new technologies that are efficient, labor-saving, and environmentally benign is being pursued. Objectives: To evaluate the secondary metabolites present in the selected Cucurbita moschata and Ipomoea batatas herbal plant (Leaf) extracts with five solvents namely ethanol, chloroform, acetone, petroleum ether, and water. To determine the antimicrobial activity of plant extracts against selected bacterial strains and assess the effect of fortified mulberry leaves with plants on the growth of silkworms and their weight of cocoon, pupa, shell, and shell ratio of silkworm Bombyx mori. Method: In this study, the selected herbal plants (Cucurbita moschata and Ipomoea batatas) were collected by hand-picking method from Singaneri village, Nanguneri Taluk, Tirunelveli districts, Tamil Nadu, India. The qualitative phytochemical analyses of selected herbal plant extracts were performed using standard procedures. Results: Phytochemicals results revealed that the different extracts (petroleum ether, chloroform, acetone, ethanol, and water extracts) revealed that, phenolic compounds, steroids, saponins, and xanthoproteins were present in the acetone extract. In petroleum ether tannins, saponins, pholobatanins, cardiac glycosides, phenolic compounds, flavanoids, carbohydrates, and xanthoproteins were present. In the antibacterial activity, ethanol and acetone extracts showed significant inhibitory effects against the pathogens viz., Enterococcus, E.coli, Aceto bactor and Bacillus cereus extracts did not show any activity. Moderate activity was expressed by ethanol extracts of I. batatasa gainst E.coli and Acetobactor (8.1±0.3mm diameter) concerning petroleum ether extracts. C. moschata revealed high activity against E.coli and Acetobactor with diameter of inhibition greater than 13.0±0.2 mm while C. moschata exhibited only moderate activity against E.coli and Acetobactor. Conclusion: The selected herbal plant extracts could increase some biological characteristics of silkworm B. mori, but this enhancement could economically improve the sericulture goals. The growers might be offered this substance to help them produce more silk.